2018
DOI: 10.3389/fpls.2018.00425
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteome Analysis of Wheat Flag Leaves and Developing Grains Under Water Deficit

Abstract: In this study, we performed the first comparative proteomic analysis of wheat flag leaves and developing grains in response to drought stress. Drought stress caused a significant decrease in several important physiological and biochemical parameters and grain yield traits, particularly those related to photosynthesis and starch biosynthesis. In contrast, some key indicators related to drought stress were significantly increased, including malondialdehyde, soluble sugar, proline, glycine betaine, abscisic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 78 publications
6
41
0
Order By: Relevance
“…Under water deficit, the soil moisture content measured in the soil layers from 0–100 cm at the grain flowering stage and 0–160 cm at the mature stage in the treatment group was significantly lower than that of the control group, particularly in soil layers from 0–40 cm (Fig. S2 in the supporting information), indicating a mild to severe drought stress during grain development based on the grade of agricultural drought (GB/T 32136–2015) …”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Under water deficit, the soil moisture content measured in the soil layers from 0–100 cm at the grain flowering stage and 0–160 cm at the mature stage in the treatment group was significantly lower than that of the control group, particularly in soil layers from 0–40 cm (Fig. S2 in the supporting information), indicating a mild to severe drought stress during grain development based on the grade of agricultural drought (GB/T 32136–2015) …”
Section: Resultsmentioning
confidence: 93%
“…Our results also showed that water deficit significantly increased the protein content and farinograph parameters in both Zhongmai175 and Jimai 22 (Table ). It is generally accepted that carbon metabolism is more sensitive to drought stress than nitrogen metabolism, resulting in a decrease in starch biosynthesis and an increase in protein content . However, the effects of drought stress on noodle and steamed bread qualities are still not clear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under global climate change and climate warming, the frequency and duration of extreme drought events is increasing faster than previously predicted [8]. Drought stress disrupts cell homeostasis and generally induces a number of morphological, physiological, and biochemical changes in all plant organs [9], particularly affecting leaf photosynthesis and transfer of stored carbohydrates [10]. Under drought stress, plants typically close the stomata, reducing evaporative treatment resulted in a significant decrease in RWC, chlorophyll content and Pn, whereas the high-N fertilizer and combined treatments showed a significant increase in chlorophyll content and Pn.…”
Section: Introductionmentioning
confidence: 99%